The Effects of Undergraduate Research Experiences as Reported by Texas A&M University System Louis Stokes Alliance for Minority Participation Students - Preuss, Michael; Merriweather, Samuel; Avila, John; Butler-Purry, Karen; Watson, Karan; Walton, Shannon; Obiomon, Pamela; Pezold, Frank; Murry, Jasmine; Roth, Michele; Kelley, Judy; Lamm, Harriet (Frontiers in Education, 2022)
In 1991, the Texas A&M University System was one of the first six Louis Stokes Alliance for Minority Participation (LSAMP) awardees. In the three decades of programming, several high impact practices (HIP) have been emphasized. One of them, undergraduate research (UR), is discussed. All members of the Alliance are part of the Texas A&M University System and undergraduate research was supported through a variety of initiatives on the Alliance campuses. Data presented chronicle student perspectives. Topics addressed are the impact of involvement in undergraduate research on academic outcomes, interest in further engagement with research, interest in graduate school, and career goals as well as the patterns of research engagement participants experienced and the forms of learning that resulted. These materials are presented regarding an audience that was overwhelmingly underrepresented minority students all of whom were pursuing science, technology, engineering, or mathematics (STEM) degrees. Students reported UR influenced their academic outcomes, further engagement with research, interest in graduate school, and career goals while facilitating learning and skill development. These findings, for URM students from institutions with three different Carnegie classifications that are a predominantly white institution, two Hispanic-serving institutions (HSIs), and a historically Black college or university (HBCU), parallel outcomes reported in the literature for investigations focused on general student populations suggesting that UR benefits are generalizable regardless of institution type and ethnicity/race of the participant. Findings also suggest that these patterns apply regardless of the student’s year in school. Material presented details the research elements commonly included in TAMUS LSAMP UR experiences and in which areas students reported the most learning. Thus, this document touches on topics important in addressing development of an adequate, well-trained, and diverse STEM workforce. It also confirms the efficacy of a highly replicable approach to facilitating a HIP, undergraduate research, with students from underrepresented groups.